Parenting di Masa Covid 19 Untuk Meningkatkan Chemistry antara Orangtua dan Anak di Desa Widoro Karangsambung Kebumen - Aryanto, Aris; Sriyono, Sriyono; Wibowo, Teguh; Danti, Vivi Inta (ADPERTISI, 2022)
The family is the child's personal shaper because the most time children spend at home with their parents. Good parents are parents who can apply parenting and can meet the physical and emotional needs of children so that they can grow and develop properly. The purpose of holding this parenting program is so that the community service team knows what problems parents face in Widoro village in accompanying their children, so that this activity can help find solutions and reduce parents' problems regarding parenting. In addition, this parenting activity is held to increase the chemistry between parents and their children. This activity was carried out in Widoro village with the target of mothers who have school-age children. According to the survey results that have been conducted, many parents are busy working and spend less time with their children, so that children are difficult to manage and do not listen to what their parents are told because children play gadgets more often than interact with their parents. After the parenting program is carried out, parents can find out good parenting patterns